Impact of agricultural research on poverty alleviation: conceptual framework with illustrations from the literature - Kerr, John M.; Kolavalli, Shashidhara (International Food Policy Research Institute, 1999)
This paper reviews the literature on the subject of the role of improved agricultural technology in alleviating poverty in developing countries. Focusing primarily on improved cultivars produced by the international agricultural research system, it shows how new technology combines with other socioeconomic and institutional factors to determine poverty alleviation utcomes. Technology’s role in alleviating poverty is both indirect and partial; technology alone cannot overcome poverty, nor can continued poverty be blamed on improved technology. The review is organized into three parts: Part I introduces poverty and the achievements of agricultural research. Part II provides a conceptual framework and evidence from the literature for the link between new agricultural technology and poverty alleviation. It takes a historical perspective, examining evidence from the literature. The discussion simplifies the complexity of the relationship between technological change and poverty alleviation by breaking it into four types of linkages: i) distribution of benefits across farms with different resource (particularly land) endowments, ii) distribution between farmers and laborers, iii) effects on food availability and consumption, and iv) impact on broader economic growth and employment. Part III looks ahead to the future. It examines potential opportunities to focus agricultural research specifically on the needs of poor people